Impact of virtual classrooms in the training of human talent in health at the General Teaching Hospital of Calderón-Ecuador - Olmedo-Pérez, Luis (2023)
An analysis is presented of the impact caused by the new study modality through virtual classrooms in the training of health professionals, who as a result of the covid-19 pandemic suspended their face-to-face academic activity, starting classes through a virtual classroom platform. The period corresponds from March 2020 to June 2021, with the aim of identifying the impact on health training and whether this modality is appropriate in their careers. For this purpose, quantitative research was conducted with the application of an anonymized survey directed to teachers and undergraduate and rotating internship students of Medicine, Obstetrics and Nursing of the cohorts of May 2020-April 2021 and September 2020-August 2021 of the Faculty of Medical Sciences of the Central University of Ecuador and who fulfill their assistance and academic activities in the General Teaching Hospital of Calderón (HGDC). The total population of teachers and students in the reference period was 365 participants and an effective sample of 175 participants was selected. The research provides a series of conclusions and suggestions that can be adopted by Higher Education Institutions (HEI) in order to improve the training of aspiring health professionals who are currently under this new virtual study modality.